Leishmaniose Tegumentar: aspectos clínicos, epidemiológicos e análise espacial no estado do Maranhão (2011 a 2022) - BUSSINGUER, Pamela Rioli Rios (2024)
Tegumentary leishmaniasis (TL) is a re-emerging and neglected disease, with new outbreaks reported worldwide, constituting a growing public health problem with repercussions in the economic and social sectors due to its scale and consequences for human health. With this in mind, the aim was to analyze the clinical-epidemiological aspects and spatial distribution of TL in the state of Maranhão from 2011 to 2022. This is an ecological and time series study, with data provided by the Maranhão State Health Department, contained in the National Notifiable Diseases System, through the Superintendence of Epidemiology and Disease Control. A descriptive analysis of the sociodemographic and clinical-epidemiological characteristics of the notified cases was carried out. Simple and multiple logistic regression models and odds ratios were used to identify the factors associated with the mucosal clinical form, using the Statistical Package for Social Sciences software, with a 5% significance level. Incidence rates were determined for each year and municipality of the Regional Health Units, and trend analysis was then carried out using Prais-Winsten regression. The incidence rates were distributed and represented spatially on maps, produced using Qgis software version 3.22.3. Global Moran and Local Moran analysis was used to analyze the spatial dependence of the data, using GeoDa software version 1.22. The research was approved by the Ethics Committee for Research Involving Human Beings of the Federal University of Maranhão. A total of 20,804 cases were reported, of which 16,468 were new and 156 were discarded due to a change in diagnosis, totaling 16,312 valid notifications. The disease mainly affected males (70.75%), brown people (71.62%), those aged between 20 and 59 (63.97%), those living in rural areas (58.55%) and those with low levels of education - illiterate or with incomplete primary education (47.58%). The most common clinical form was cutaneous (96.80%), diagnosed in 77.69% of cases by laboratory criteria. The minority of cases (0.95%) had HIV co-infection, 78.07% of patients progressed to cure, while only 0.05% died from TL, and in the rest, this was attributed to other causes. In the univariate logistic regression analysis of mucosal cases, only the area of residence and the parasitological laboratory result showed no significant association. However, in the multivariate analysis, age between 31 and 45, age between 46 and 60, male gender, co-infection with HIV and positive and compatible histopathological laboratory showed statistically significant associations with the mucosal form of the disease, indicating that they are risk factors for this clinical presentation. Investigation of geographical distribution revealed a downward trend in incidence over the years, with no municipality showing an upward trend. The analysis of high-high risk clusters identified patterns of spatial grouping of cases in different periods, highlighting areas of greater vulnerability in the west and north of Maranhão. Given these findings, comprehensive strategies are needed that include strengthening epidemiological surveillance for early identification of cases in high-risk areas, community education for prevention and awareness, strict vector control measures, such as the use of insecticides and environmental management, and ensuring access to effective diagnosis and treatment, prioritizing those most susceptible to the mucosal form of the disease.